A simple method for environmental cell depressurization for use with an electron microscope. (9th August 2017) - Ogawa, Naoki; Mizokawa, Ryo; Saito, Minoru; Ishikawa, Akira
Abstract : With attaching a balloon structure to the specimen holder, the pressure in the environmental cell of SEM can be depressurized from 1 to 0.01 atm to improve the image resolution. This simple system can be applied to various electron microscopes by only modifying the specimen holder. Abstract: With the aid of the environmental cell (EC) in electron microscopy, hydrated specimens have been observed at high resolutions that optical microscopy cannot attain. Due to the ultra-high vacuum conditions of the inner column of the electron microscope, the EC requires sealing films that are sufficiently thin to allow electron transmission and that are sufficiently tough to withstand the pressure difference between the inside and outside of the EC. However, most hydrated specimens can be observed at low vacuum because the saturated vapor pressure of water is known to be 0.02 atm at room temperature. These concepts have been used in the differential pumping system, but it is complicated and relatively expensive. In this work, we propose a simple method for depressurization of the EC using a ' balloon structure ' and demonstrate the theoretical benefits and practical improvement for specimen observations in low-vacuum conditions.